Teacher factors influencing Grade 12 Accounting learners’ performance in the Eswatini General Certificate Secondary Examination - Msizi Vitalis Mkhize; Muntuwenkosi Abraham Mtshali; Khumbuzile Sithebe (Perspectives in Education, 2022)
This study examined the influence of teacher-related factors on Grade 12 Accounting learners’ performance in the Accounting General Certificate Secondary Examination (GCSE) in Eswatini. A sequential, explanatory, mixed-methods design was employed. A stratified random sample for the quantitative phase comprised 400 Accounting learners and 80 Accounting teachers from 10 schools performing well, and from 10 schools performing poorly. Purposive sampling was used for the qualitative phase to select 6 learners and 4 teachers from schools performing well, and 6 learners and 4 teachers from schools performing poorly to participate in the study. The data collection instruments were questionnaires and semi-structured interviews. Quantitative data were analysed using Statistical Package for Social Sciences (SPSS), while qualitative data were analysed thematically. The study revealed that teacher variables affecting learners’ performance in Grade 12 Accounting GCSE in Eswatini were teachers’ attitude, teachers’ absenteeism, non-completion of the syllabus, revision before the examination,assignments to learners, and regularly giving up-to-standard tests. The researcher recommended inter alia that teachers should teach the relevant Accounting content thoroughly during the first and second terms so that enough time is available for revision intended to address knowledge gaps that may occur as a result of learners having not understood some content during the teaching sessions.